Comparison of the IOLMaster 700 and the Pentacam in the Analysis of the Lens Nuclear Density Before the Cataract Surgery - Li, Bowen; Liu, Yuqi; Hu, Yiping; Shi, Mingyu (Frontiers in Medicine, 2021)
Purpose: To evaluate the difference of lens nuclear density measured before and after mydriasis using IOLMaster700 and Pentacam Scheimpflug imaging, and investigate the relationship between the measurement data and phacoemulsification parameters. Methods: Patients with age-related nuclear cataract diagnosed on slit-lamp examination were enrolled in the age range of 53 to 76 years. No patient had a history of ocular surgery, laser treatment or general disorders affecting vision. The mean optical density (OD) was measured by IOLMaster700 using Image-Pro® Plus software before and after mydriasis. Pentacam nucleus densitometry (PND) was obtained automatically from Pentacam Scheimpflug imaging and compared with OD. The correlation between OD and effective phaco time (EPT), PND and EPT were analyzed respectively. Results: In our study, 53 eyes of 52 patients were evaluated. Before and after mydriasis, the mean OD values were 64.34 ± 23.31 and 63.81 ± 23.21 pixel units respectively, the mean PND values were 28.51±11.42 and 25.41 ± 11.31 respectively, the mean EPT value was 6.24±3.49. The Bland Altman analysis showed that lens nuclear densities of the two devices were highly consistent. There was no significant difference in OD values (t=0.455, P>0.05) before and after mydriasis, but the difference has existed in PND values (t=2.509, P<0.05). The OD and PND values were positively correlated with EPT before and after mydriasis (rOD-Before=0.604, rOD-After=0.593, rPND-Before=0.701 and rPND-After=0.891, P＜0.01). Conclusion: The combination of IOLMaster700 and Image Pro®Plus software can quantitatively evaluate the degree of cataract lens opacification. It has good consistency with Pentacam and is positively correlated with phacoemulsification parameters. It is expected to become a new method to predict phacoemulsification parameters before and during cataract surgery.